Nanobacteria in clouds can spread oral pathologic calcifications around the world - Jafar Kolahi; Mahdi Shahmoradi; Molood Sadreshkevary (Wolters Kluwer Medknow Publications, 2012)
Introduction: Nanobacteria (calcifying nanoparticles, nanobes) are one of the most controversial issues in contemporary biology. Studies show accumulating evidence on association of nanobacteria with oral pathologic calcifications such as calculus, pulp stone, and salivary gland stones. The Hypothesis: Experiments have shown that nanobacteria are excreted from the body in urine and saliva, lifted from the ground by winds into the cloud, and transit between the high humidity region of the clouds and the relatively dry inter-cloud regions. Remnants of a sticky protein coating that nanobacteria make it act as an extremely efficient cloud condensation nuclei. Following condensation of cloud, nanobacteria return to the earth via rain and snow. Evaluation of the Hypothesis: Transmission of nanobacteria via clouds is not surprising when compared with cosmic transmission of nanobacteria. The apatite mineral layer around the organism serves as a primary defence shield against various seriously life-threatening conditions. A double defence with the apatite layer and an impermeable membrane combined with a very slow metabolism is a likely explanation for the resistance of nanobacteria.